Examining Fall Risk and Related Factors in Rural Older Adults: A Cross-sectional Study in Yazd Province, Iran - Masoumeh Abbasi-Shavazi; Sara Jambarsang; Zainab Anbari-Nogyni; Hosseinali Sadeghian; Vida Sadat Anoosheh (علوم بهداشتی ایران)
Background and Purpose: Given the high prevalence of age-related diseases and physiological changes in addition to the susceptibility of the elderly to falls, this issue has become a major public health problem. This study assesses the risk of falls and related factors among the elderly living in rural areas. Materials and Methods: This cross-sectional study was conducted on 302 elderly people in rural areas of Yazd Province, Iran, using the multi-stage sampling method. They completed a multi-section questionnaire, including demographic questions and the Tinetti gait and balance scale for assessing gait and balance in the elderly. The data were entered into the SPSS software, version 20 and analyzed by the chi-square test and ordinal logistic regression model. The statistical significance level of P<0.05 was considered in all tests. Results: The results showed that 38.1% of the participants presented a high fall risk, 20.5% demonstrated medium risk and 41.4% showed a low fall risk. Gender, age and visual status had a significant relationship with the risk of falls in the elderly (P<0.05). The probability of falls in women was 2.6 times higher compared to men. Moreover, the likelihood of falls in people with visual impairment was 1.7 times higher compared to subjects with no visual impairment and the probability of falls increased by 15% as they aged. Conclusion: Visual impairment, gender, and age factors are diagnosed as related risk factors for falls in rural elderly people. It is recommended to consider these factors for the greater effectiveness of interventions to reduce falls in the elderly.